Coronary sinus catalase and ceruloplasmin levels predict all-cause mortality in patients with end-stage heart failure awaiting heart transplantation. (25th November 2020) - Szczurek, W; Gasior, M; Skrzypek, M; Kubiak, G; Kuczaj, A; Szygula Jurkiewicz, B
Abstract: : Background, As a consequence of the worldwide increase in life expectancy and due to significant progress in the pharmacological and interventional treatment of heart failure (HF), the proportion of patients that reach an advanced phase of disease is steadily growing. Hence, more and more numerous group of patients is qualified to the heart transplantation (HT), whereas the number of potential heart donors has remained invariable since years. It contributes to deepening in disproportion between the demand for organs which can possibly be transplanted and number of patients awaiting on the HT list. Therefore, accurate identification of patients who are most likely to benefit from HT is imperative due to an organ shortage and perioperative complications. Purpose: The aim of this study was to identify the factors associated with reduced survival during a 1.5-year follow-up in patients with end-stage HF awating HT. Method: We propectively analysed 85 adult patients with end-stage HF, who were accepted for HT at our institution between 2015 and 2016. During right heart catheterization, 10 ml of coronary sinus blood was additionally collected to determine the panel of oxidative stress markers. Oxidative-antioxidant balance markers included glutathione reductase (GR), glutathione peroxidase (GPx), glutathione transferase (GST), superoxide dismutase (SOD) and its mitochondrial isoenzyme (MnSOD) and cytoplasmic (Cu/ZnSOD), catalase (CAT), malondialdehyde (MDA), hydroperoxides lipid (LPH), lipofuscin (LPS), sulfhydryl groups (SH-), ceruloplasmin (CR). The study protocol was approved by the ethics committee of the Medical University of Silesia in Katowice. The endpoint of the study was mortality from any cause during a 1.5 years follow-up. Results: The median age of the patients was 53.0 (43.0–56.0) years and 90.6% of them were male. All included patients were treated optimally in accordance with the guidelines of the European Society of Cardiology. Mortality rate during the follow-up period was 40%. Multivariate logistic regression analysis showed that ceruloplasmin (odds ratio [OR] = 0.745 [0.565–0.981], p=0.0363), catalase (OR = 0.950 [0.915–0.98], p=0.0076), as well as high creatinine levels (OR = 1.071 [1.002–1.144], p=0.0422) were risk factors for death during 1.5 year follow-up. Conclusions: Coronary sinus lower ceruloplasmin and catalase levels, as well as higher creatinine level are independently associated with death during 1.5 year follow-up. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Medical University of SIlesia, Katowice, POland